The relationship of motor skills with performance: Meta-analysis study - Ahmad Muchlisin Natas Pasaribu; Juli Candra; Rizal Kamsurya; Zainur; Nurkadri; Anak Agung Ngurah Putra Laksana (UIR Press, 2021)
This study aims to test the effect size of motor skills on the performance of a person in the field of sports. The type of research used is meta-analysis Studyes. The data sources in this study are google scholar, Jurnal SINTA, Scopus, and Eric. The livelihood of literature from various sources uses the keywords motor skills and performance. Data analysis is conducted through the stages of variable identification, identification of r values, transforming the r value into the z distribution which is the size effect of each study, calculating variance, calculating the Error Standard of z, and calculating the summary effect. Summary effect calculation using Jeffreys's Amazing Statistics Program (JASP) software. The results showed that there was a significant positive correlation between motor skills and performace. The relationship of motor skills to performance falls into the moderate category with a random effect correlation value of 0.498.